Localized Piezoelectric Alveolar Decortication for Orthodontic Treatment in Adults: A Randomized Controlled Trial. (August 2016) - Charavet, C.; Lecloux, G.; Bruwier, A.; Rompen, E.; Maes, N.; Limme, M.; Lambert, F.
This randomized controlled trial aimed to evaluate the benefits and clinical outcomes of piezocision, which is a minimally invasive approach to corticotomy that is used in orthodontic treatments. Twenty-four adult patients presenting with mild overcrowdings were randomly allocated to either a control group that was treated with conventional orthodontics or a test group that received piezo-assisted orthodontics. The piezocisions were performed 1 wk week after the placement of the orthodontic appliances. Neither grafting material nor sutures were used. All patients were followed every 2 wk, and archwires were changed only when they were no longer active. The periods required for the completion of the overall orthodontic treatments were calculated, and the periodontal parameters were evaluated at baseline and at the end of the orthodontic treatment. Patient-centered outcomes were assessed with a visual analog scale; analgesic use following the procedures was also recorded. The patient characteristics were similar between the 2 groups. The overall treatment time was significantly reduced by 43% in the piezocision group as compared with the control group. In both groups, periodontal parameters (i.e., recession depth, pocket depth, plaque index, and papilla bleeding index) remained unchanged between the baseline and treatment completion time points. No increase in root resorption was observed in either group. Scars were observed in 50% of the patients in the piezocision group. Analgesic consumption was similar following orthodontic appliance placement and piezocision surgery. Patient satisfaction was significantly better in the piezocision group than in the control group. In these conditions, the piezocision technique seemed to be effective in accelerating orthodontic tooth movement. No gingival recessions were observed. The risk of residual scars might limit the indications for piezocision in patients with a high smile line (ClinicalTrials.gov NCT02590835).